Systematic review and consensus definitions for the Standardised Endpoints in Perioperative Medicine (StEP) initiative: renal endpoints - McIlroy, D R; Bellomo, R; Billings, 4th, F T; Karkouti, K; Prowle, J R; Shaw, A D; Myles, P S (British journal of anaesthesia : BJA, 2018)
Renal injury is a common perioperative complication. The adoption of renal endpoints, standardised and valid for use in perioperative clinical trials, would enhance the quality of perioperative clinical research. The Standardised Endpoints in Perioperative Medicine (StEP) initiative was established to derive standardised endpoints for use in perioperative clinical trials. A systematic review was conducted to identify renal endpoints currently reported in perioperative clinical trials. In parallel, an initial list of candidate endpoints was developed based on renal theme group expertise. A multi-round Delphi consensus process was used to refine this list and produce a suite of recommended perioperative renal outcome measures. Based on our systematic review, 63 studies were included for analysis. Marked heterogeneity and imprecision of endpoint definitions were observed. Our initial list of candidate endpoints included 10 endpoints for consideration. The response rates for Delphi rounds 1, 2, and 3 were 89% (n=16), 90% (n=75), and 100% (n=6), respectively. A final list of four renal endpoints was identified: acute kidney injury defined by the Kidney Disease: Improving Global Outcomes (KDIGO) consensus criteria, acute kidney disease defined by ≥30% decline in estimated glomerular filtration rate from baseline at 30 days after operation in patients meeting the acute-kidney-injury criteria within 7 days of surgery, the composite of death or renal replacement therapy, and the Major Adverse Kidney Events (MAKE) composite. We identified four key renal outcome measures that should be considered for use in perioperative clinical trials. Using standardised definitions to capture and report these endpoints will facilitate improved benchmarking and meta-analysis of future trials.